C. elegans orphan nuclear receptor NHR-42 represses innate immunity and promotes lipid loss downstream of HLH-30/TFEB - Goswamy, Debanjan; Gonzalez, Xavier; Labed, Sid A.; Irazoqui, Javier E. (Frontiers in Immunology, 2023)
In recent years, transcription factors of the Microphthalmia-TFE (MiT) family, including TFEB and TFE3 in mammals and HLH-30 in Caenorhabditis elegans, have emerged as important regulators of innate immunity and inflammation in invertebrates and vertebrates. Despite great strides in knowledge, the mechanisms that mediate downstream actions of MiT transcription factors in the context of innate host defense remain poorly understood. Here, we report that HLH-30, which promotes lipid droplet mobilization and host defense, induces the expression of orphan nuclear receptor NHR-42 during infection with Staphylococcus aureus. Remarkably, NHR-42 loss of function promoted host infection resistance, genetically defining NHR-42 as an HLH-30-controlled negative regulator of innate immunity. During infection, NHR-42 was required for lipid droplet loss, suggesting that it is an important effector of HLH-30 in lipid immunometabolism. Moreover, transcriptional profiling of nhr-42 mutants revealed wholesale activation of an antimicrobial signature, of which abf-2, cnc-2, and lec-11 were important for the enhanced survival of infection of nhr-42 mutants. These results advance our knowledge of the mechanisms by which MiT transcription factors promote host defense, and by analogy suggest that TFEB and TFE3 may similarly promote host defense via NHR-42-homologous nuclear receptors in mammals.